"Gjeng vegane etter dei døde". Død, dyrking og (om-)bygging av røyser i et langtidsperspektiv (AmS-Varia, 2020)
How are we to understand and interpret intentional deposits of stone built-up over long time spans? The empirical point of departure for this contribution is a complex cairn located on a hilltop in Sauherad, Telemark, excavated in 2015. Twenty C14-samples date the site from c. 300 cal. BC to the present. Additionally, a single deposition of two Neolithic thin-butted axes of Funnel Beaker type (3800–3300 BC) was uncovered. The main phase of activity is related to the Early Iron Age (c. 300 BC–AD 450). No remains of Iron Age burials were identified, but it is argued that the Neolithic axes represent a secondary deposit related to the Iron Age activity. Taking the temporal depth and durability in the practice of removing stone as a point of departure, this paper explores how gathering and placing of stones may have been accorded meaning during various points in time and focuses particularly on the relationship between stone clearance, agriculture, fertility and ancestors.